Дослідження та порівняння характеристик мікропроцесорного пристрою релейного захисту та автоматики РС83-АВ3 компанії «РЗА СИСТЕМЗ» з пристроями електромеханічного типу - Мірошник, О. О.; Мороз, О. М.; Пазій, В. Г.; Миргород, Д. Г.; Ганус, Р. О.; Галько, Сергій Віталійович; Miroshnyk, О.; Moroz, O.; Paziy, V.; Myrgorod, D.; Hanus, R.; Halko, Serhii (Запоріжжя : 2024, 2024)
UA: В статті розглянуті автоматизовані системи релейного захисту та автоматики, які працюють на базі мікропроцесорних пристроїв, що поєднують багато видів захисту та протиаварійної автоматики. Показано, що один термінал релейного захисту та автоматики здатний виконувати велику кількість функцій. Важливою особливістю сучасних пристроїв релейного захисту та автоматики є можливість інтеграції їх в інформаційну мережу, що дозволяє реалізувати концепції «Цифрова підстанція» та «Smart Grid». Виконано порівняльний аналіз характеристик мікропроцесорного пристрою РС83-АВ3 та електромеханічних пристроїв релейного захисту для визначення ефективності, надійності та технічних переваг мікропроцесорних рішень у сучасних електроенергетичних системах. EN: The article discusses automated systems of relay protection and automation, which work on the basis of microprocessor devices, combining many types of protection and emergency automation. During the operation of the electric power system, emergencies inevitably arise that disrupt the normal operation of the equipment and the system as a whole. Among the most dangerous accidents are short circuits, which can cover large areas of the network and can have quite serious consequences for the entire electricity system. Such emergencies are especially risky during martial law, when the energy infrastructure is constantly under attack, has a reduced resource, reduced reliability, but the requirements for it, on the contrary, are increased, since in addition to ensuring the operation of communications, banks, and government agencies, it is also necessary to provide the population with water supply and heat supply, especially in winter. To localize damaged elements and prevent the development of accidents in the electric power system, relay protection and automation devices are used, which play a decisive role in maintaining stable and safe operation of the electric power system and ensuring reliable power supply. Today, traditional relay protection is being replaced by microprocessor devices that combine protection, automation, control and alarm functions. Their use increases the sensitivity of protection and shortens the response time, which reduces the damage from power outages. It is also possible to create automated substation control systems and integrate them with automated control systems of the upper level. This opens up prospects for the use of microprocessor terminal devices as the main relay protection devices in electrical networks for further advancement to the ideal Smart Grid model. It is shown that one relay protection and automation terminal is capable of performing a large number of functions. An important feature of modern devices of relay protection and automation is the possibility of their integration into the information network, which allows to implement the concepts of "Digital Substation" and "Smart Grid". A comparative analysis of the characteristics of the РС83-АВ3 microprocessor device and electromechanical relay protection devices was performed to determine the efficiency, reliability and technical advantages of microprocessor solutions in modern power systems.
Research and comparison of characteristics of the microprocessor relay protection and automation device РС83-АВ3 company "RPA SYSTEMS" with electromechanical devices
Keywords: мікропроцесорний пристрій релейного захисту; Smart Grid; цифрова підстанція; електроенергетична система; коротке замикання; microprocessor relay protection device; digital substation; electric power system; short circuit